Government Contracting and Living Wages > Minimum Wages - Nikhil Datta; Stephen Machin (Institute of Labor Economics (IZA), 2024)
Government procurement accounts for a significant share of GDP, and environmental, social and corporate governance (ESG) clauses in government contracts have become common across developed economies. This paper studies one of these clauses: living wages that are set considerably higher than mandated minimum wages. When a local government in the UK signs up to become a living wage employer, as a significant number did in the time period we study, firms that have procurement contracts with them have to pay workers the living wage. This variation is studied with rich matched data on workers in establishments for a service sector company with many establishments located across the country. Just under half of the firm's establishments were made to comply with the living wage as a consequence of the local government becoming a living wage employer in the period between 2011 and 2019. In a staggered difference-in-differences research design, low wage workers are shown to receive a significant wage boost from the living wage introduction. Consistent with a model of monopsony power and where bottom-of-the-rung workers and supervisors are gross complements, the living wage induced labour-labour substitution in favour of the former. Further adjustment to the wage bill increase from the introduction of the living wage took place through within-establishment internal changes to the establishment pay policy structures. The overall result was that the Company was able to absorb the wage cost shock embodied in living wage adoption in a way that significantly narrowed establishment wage inequality.
Keywords: J31; J38; J42; 330; government contracting; living wages